Prognostic Value of Vimentin Is Associated With Immunosuppression in Metastatic Renal Cell Carcinoma - Yao, Jia xi; Chen, Xiang; Zhu, Yan jun; Wang, Hang; Hu, Xiao yi; Guo, Jian ming (Frontiers in Oncology, 2020)
Introduction: Vimentin, a classical marker of epithelial–mesenchymal transition, reflects the invasiveness of cancer cells. Its role in the genesis and progression of tumor has been reported in various cancers, including renal cell carcinoma. However, the impact of vimentin on tumor microenvironment, particularly its implication with tumor-infiltrating immune cells, is unknown. Methods: We conducted this study in 231 patients with metastatic renal cell carcinoma (mRCC) to determine the potential relationship between vimentin and immune status. Using immunohistochemical staining, expression of vimentin, CD8, FOXP3, programmed cell death protein 1 (PD-1), and programmed cell death ligand 1 (PD-L1) were evaluated in resected tumor tissue. Kaplan–Meier analysis and Cox regression models were used for survival analysis. Chi-square test, Fisher exact test, and Mann–Whitney U-test were used for comparison between vimentin high and low groups. Results: High expression of vimentin, stroma PD-L1, and PD-1 indicated poor overall survival, whereas low regulatory T cell or high CD8+ T cell infiltration indicated long overall survival. Stroma PD-L1 (P = 0.030), vimentin (P = 0.026) expression, and CD8+ T cell infiltration (P < 0.001) were independent prognostic factors in mRCC. High vimentin expression was accompanied by high PD-1, PD-L1 expression, and increased regulatory T cell infiltration (all P < 0.001), indicating immunosuppression in the tumor microenvironment. Conclusions: We revealed that vimentin expression was associated with immunosuppression in mRCC, and the immune-suppressive status might be possibly posed by PD-1/PD-L1. Patients with high vimentin expression may acquire potential benefit from the recently approved PD-1/PD-L1 inhibitors. However, further clinical trials are needed to validate our findings.